Short-Term Impacts of Formalization Assistance and a Bank Information Session on Business Registration and Access to Finance in Malawi - Campos, Francisco (World Bank, Washington, DC, 2016)
Despite regulatory efforts designed to make it easier for firms to formalize, informality remains extremely high among firms in Sub-Saharan Africa. In most of the region, business registration in a national registry is separate from tax registration. This paper provides initial results from an experiment in Malawi that randomly allocated firms into a control group and three treatment groups: a) a group offered assistance for costless business registration; b) a group offered assistance with costless business registration and (separate) tax registration; and c) a group offered assistance for costless business registration along with an information session at a bank that ended with the offer of business bank accounts. The study finds that all three treatments had extremely large impacts on business registration, with 75 percent of those offered assistance receiving a business registration certificate. The findings offer a cost-effective way of getting firms to formalize in this dimension. However, in common with other studies, information and assistance has a limited impact on tax registration. The paper measures the short-term impacts of formalization on financial access and usage. Business registration alone has no impact for either men or women on bank account usage, savings, or credit. However, the combination of formalization assistance and the bank information session results in significant impacts on having a business bank account, financial practices, savings, and use of complementary financial products.